Autologous Blood Transfusion after Local Infiltration Analgesia with Ropivacaine in Total Knee and Hip Arthroplasty - Torben Breindahl; Ole Simonsen; Peter Hindersson; Bjarne Brødsgaard Dencker; Mogens Brouw Jørgensen; Sten Rasmussen (Anesthesiology Research and Practice)
Aims. To study the safety of autotransfusion following local infiltration analgesia (LIA) with ropivacaine. Background. Knowledge of blood concentrations of ropivacaine after LIA and autotransfusion is crucial. However, very limited data are available for toxicological risk assessment. Methods. Autotransfusion was studied in patients after total knee arthroplasty (TKA: n=25) and total hip arthroplasty (THA: n=27) with LIA using 200 mg ropivacaine, supplemented with two postoperative bolus injections (150 mg ropivacaine). Drainage blood was reinfused within 6 h postoperatively. Results. Reinfusion caused a significant increase in the serum concentration of total ropivacaine for TKA from 0.54±0.17 (mean ± SD) to 0.79±0.20 μg/mL (P<0.001) and a nonsignificant increase for THA from 0.62±0.17 to 0.63±0.18 μg/mL. The maximum free (unbound) concentration after reinfusion was 0.038 μg/mL. Peak total and free venous ropivacaine concentrations after 8 h and 16 h postoperative bolus injections were 2.6 μg/mL and 0.11 μg/mL, respectively. All concentrations observed were below the threshold for toxicity and no side effects were observed. Conclusion. Autotransfusion of patients undergoing knee or hip arthroplasty after local infiltration analgesia with 200 mg ropivacaine can be performed safely, even supplemented with 8 h and 16 h postoperative bolus injections.